2001
DOI: 10.1136/jcp.54.9.684
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of candidate gene product expression in the duodenal epithelium of children with coeliac sprue

Abstract: Background-Coeliac sprue is a chronic disease, in which there is a characteristic mucosal lesion of the small intestine and impaired nutrient absorption, which improves upon the withdrawal of wheat gliadins and related grain proteins from the diet. Biopsy specimens demonstrate diffuse enteritis with pronounced atrophy or total loss of villi. There is also a long term risk of malignant disease. Aims-To compare the immunoexpression of DCC (deleted in colon cancer), p53, E-cadherin, and -catenin in the duodenal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
1
11
1
Order By: Relevance
“…46 Taken together, our results extend our knowledge on epithelial modification in CD and suggest that the disruption of AJs might be a direct consequence of cytokine action, whereas that of TJs probably also is influenced by apoptotic stimuli. The explanation for the discrepancy with the conclusions of other authors [31][32][33][34] lies mainly in the use of different techniques or antibodies with different epitope targets, as in the original design of our study targeting the coimmunoprecipitation and colocalization of the junctional components. With this aim, we considered the expression of the specific proteins after an immunoprecipitation step performed by using the cytoplasmic components of TJs and AJs, and, in accordance with our results, other authors did not find changes in E-cadherin expression in childhood CD.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…46 Taken together, our results extend our knowledge on epithelial modification in CD and suggest that the disruption of AJs might be a direct consequence of cytokine action, whereas that of TJs probably also is influenced by apoptotic stimuli. The explanation for the discrepancy with the conclusions of other authors [31][32][33][34] lies mainly in the use of different techniques or antibodies with different epitope targets, as in the original design of our study targeting the coimmunoprecipitation and colocalization of the junctional components. With this aim, we considered the expression of the specific proteins after an immunoprecipitation step performed by using the cytoplasmic components of TJs and AJs, and, in accordance with our results, other authors did not find changes in E-cadherin expression in childhood CD.…”
Section: Discussioncontrasting
confidence: 83%
“…Indeed, a reduction in depth and number of strands of TJ in active disease first was demonstrated by using the freeze-fracture electron microscopy technique in the late 1970s 28 and subsequently was confirmed, 29,30 together with the suggestion of down-regulation of ZO-1 expression. 31,32 As for the AJs, a significant reduction of E-cadherin and β-catenin expression, which returns to normal levels after following a gluten-free diet, was reported in children 33 and adults with untreated CD. 34 The present study, the only one that used coimmunoprecipitation and colocalization techniques, clearly demonstrated that in active disease, the absence of tyrosine-phosphorylated ZO-1 makes it unable to join occludin and to localize at the apical end of the lateral membrane, as appeared evident in confocal microscopy in which the TJ complex proved to be disrupted.…”
Section: Discussionmentioning
confidence: 97%
“…These findings, and the pattern of predominant focal surface and not crypt reduction, are identical to those in coeliac disease. 22 E-cadherin is also the binding site for the integrin found exclusively on intra-epithelial lymphocytes, aEb7 or CD103. 23 Homing of these lymphocytes to the intestinal epithelium is dependent on this interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Diseases associated with mutations in tight junction proteins have been described. E-Cadherin and βcatenin are reportedly decreased in celiac disease (Barshack et al 2001 ). The arrowhead indicates the tight junction (TJ), the thin arrow the adherens junction, or zonula adherens, and the thick lower arrow the desmosomes.…”
Section: The Intestinal Intercellular Junctionmentioning
confidence: 99%